Significant improvement of bone marrow-derived MSC expansion from MDS patients by defined xeno-free medium - Altrock, Eva; Sens-Albert, Carla; Hofmann, Franziska; Riabov, Vladimir; Schmitt, Nanni; Xu, Qingyu; Jann, Johann-Christoph; Rapp, Felicitas; Steiner, Laurenz; Streuer, Alexander; Nowak, Verena; Obländer, Julia; et al. (Stem cell research & therapy, 2023)
Robust and reliable in vitro and in vivo models of primary cells are necessary to study the pathomechanisms of Myelodysplastic Neoplasms (MDS) and identify novel therapeutic strategies. MDS-derived hematopoietic stem and progenitor cells (HSPCs) are reliant on the support of bone marrow (BM) derived mesenchymal stroma cells (MSCs). Therefore, isolation and expansion of MCSs are essential for successfully modeling this disease. For the clinical use of healthy MSCs isolated from human BM, umbilical cord blood or adipose tissue, several studies showed that xeno-free (XF) culture conditions resulted in superior growth kinetics compared to MSCs cultured in the presence of fetal bovine serum (FBS). In this present study, we investigate, whether the replacement of a commercially available MSC expansion medium containing FBS with a XF medium is beneficial for the expansion of MSCs derived from BM of MDS patients which are often difficult to cultivate.
Gesehen am 20.07.2023